Reclassification of four aubrites as enstatite chondrite impact melts: Potential geochemical analogs for Mercury. (19th February 2019) - Udry, Arya; Wilbur, Zoë E.; Rahib, Rachel R.; McCubbin, Francis M.; Vander Kaaden, Kathleen E.; McCoy, Timothy J.; Ziegler, Karen; Gross, Juliane; DeFelice, Christopher; Combs, Logan; Turrin, Brent D.
Abstract: We present petrologic and isotopic data on Northwest Africa (NWA) 4799, NWA 7809, NWA 7214, and NWA 11071 meteorites, which were previously classified as aubrites. These four meteorites contain between 31 and 56 vol% of equigranular, nearly endmember enstatite, Fe, Ni metal, plagioclase, terrestrial alteration products, and sulfides, such as troilite, niningerite, daubréelite, oldhamite, and caswellsilverite. The equigranular texture of the enstatite and the presence of the metal surrounding enstatite indicate that these rocks were not formed through igneous processes like the aubrites, but rather by impact processes. In addition, the presence of pre‐terrestrially weathered metal (7.1–14 vol%), undifferentiated modal abundances compared to enstatite chondrites, presence of graphite, absence of diopside and forsterite, low Ti in troilite, and high Si in Fe, Ni metals suggest that these rocks formed through impact melting on chondritic and not aubritic parent bodies. Formation of these meteorites on a parent body with similar properties to the EHa enstatite chondrite parent body is suggested by their mineralogy. These parent bodies have undergone impact events from at least 4.5 Ga (NWA 11071) until at least 4.2 Ga (NWA 4799) according to 39 Ar‐ 40 Ar ages, indicating that this region of the solar system was heavily bombarded early in its history. By comparing NWA enstatite chondrite impact melts to Mercury, we infer that they represent imperfect petrological analogs to this planet given their high metal abundances, but they could represent important geochemical analogs for the behavior and geochemical affinities of elements on Mercury. Furthermore, the enstatite chondrite impact melts represent an important petrological analog for understanding high‐temperature processes and impact processes on Mercury, due to their similar mineralogies, Fe‐metal‐rich and FeO‐poor silicate abundances, and low oxygen fugacity.